Stability assessment and laboratory scale fermentation of pastes produced on a pilot scale from mealworms (Tenebrio molitor). (March 2019) - De Smet, J.; Lenaerts, S.; Borremans, A.; Scholliers, J.; Van Der Borght, M.; Van Campenhout, L.
Abstract: European consumers generally still have a reluctant attitude towards the consumption of insects. One strategy to trigger the willingness to consume edible insects is to process them invisibly in familiar foodstuffs. To facilitate this, insects need to be processed to intermediates that can be incorporated readily in products by the food industry. To this end, a mealworm paste that was free of tastable exoskeleton particles was manufactured successfully using industrial equipment. Of this novel intermediate the proximate and fatty acid composition, moisture content, water activity, pH, viscosity, peroxide and p -anisidine values and colour was analysed. Next, the impact of storage temperature (4 °C and −21 °C) and presence of preservatives (sodium nitrite and sodium lactate) on the chemical and microbial stability of the paste were evaluated, as well as its fermentability to assess the most suited preservation strategy. During storage at −21 °C, all tested parameters remained constant for three months, except for some fat oxidation. At 4 °C, substantial microbial growth was observed during three weeks of storage, regardless of the use of preservatives. Finally, the paste was also shown to be suited for fermentation. Future research should assess whether fermentation can extend the storage time and/or improve the product quality. Highlights: Mealworm paste without exoskeleton particles can be produced in industrial equipment. Storage at −21 °C ensures colour, viscosity and microbial stability for 3 months. Storage at 4 °C does not ensure microbial stability during 3 weeks of storage. The two tested preservatives did not increase the microbial stability of the paste. The mealworm paste can be fermented using a commercial meat starter culture.